Role Playing Learning Methods Integrated Inquiry Approach In Improving Interest Of Grade V Elementary School Students - Ridha Fitria; Sri Hastati (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This research is the background of the low interest in learning of grade V students of SD Inpres Bontojai Makassar City which is caused by the learning process that is still dominated by the teacher's explanation (lecture method), so that students are less focused, passive, and less confident when appearing in front of the class. This research aims to increase students' interest in learning through the application of the Role Playing learning method integrated with an inquiry approach. The type of research used is Class Action Research (PTK) which is carried out in two cycles. The subject of this study is a grade V student of SD Inpres Bontojai, Makassar City. Data collection techniques are carried out through observation, interviews, and documentation. The data obtained was then analyzed using qualitative data analysis techniques and supported by quantitative data. The results of the study showed a significant increase in student learning interest from cycle I to cycle II. In the first cycle, students' interest and learning activities have begun to be seen but are not optimal because some students still feel embarrassed and lack confidence in role-playing. In cycle II, the development of student behavior has increased optimally; Students become more active, dare to ask questions, confident, and enthusiastic about learning. This success is evidenced by the percentage of student learning activities through the inquiry approach in cycle II which reached the good category, with details on Pancasila Education subjects of 76.42%, Mathematics of 78.125%, and Indonesian of 75.85%. Meanwhile, role playing in the second cycle reached the good category, with details on Pancasila Education subjects of 80.68%, Mathematics of 86.80%, and Indonesian language of 85.79%. Based on these results, it can be concluded that the application of the integrated Role Playing Learning method with an inquiry approach is able to significantly increase the learning interest of grade V students of SD Inpres Bontojai, Makassar City.